On the solution of the Riccati equation by the decomposition method - Bulut, H; Evans, DJ (Taylor & Francis Ltd, 2002)
In this paper we study an analytic solution and a reliable numerical approximation of the Riccati equation by using the Adomian's decomposition method. The solution is calculated in the form of a series with easily computable components, The numerical results show the effectiveness of the method for this type of equation. Comparing the methodology with some known techniques shows that the present approach is relatively easy and highly accurate.
Keywords: Riccati equation; Adomian decomposition; Runge-Kutta method